APPLICATION OF UTAUT THEORY (UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY) TO KNOW THE USE BEHAVIOR OF UPN SCIENCE E-LEARNING USERS WITH BEHAVIORAL INTENTION AS INTERVENING VARIABLES - Aida Uyun Salsabil; Nurul Azizah (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2022)
This study aims to determine: (1) the effect of Performance Expectancy, Effort Expectancy, Social Influence, Perceived Ease of Use, Perceived Usefulness on the Behavioral Intention of UPN Science e-learning users; (2) Effect of Faciliating Condition and Behavioral Intention on Use Behavior of UPN Science e-learning users. The population in this study were UPN Veterans East Java students who used e-learning in UPN Science. In this study using a sample of 266 respondents. The sampling technique in this study is the purposive sampling technique with the criteria of UPN Veterans East Java students using UPN Science in their learning process. The data analysis technique uses Partial Least Square using smartPLS 3.0 software.The results of this study indicate that Performance Expectancy, Effort Expectancy, Social Influence, Perceived Ease of Use, Perceived Usefulness have a positive and significant influence on Behavioral Intention. Likewise, Faciliating Condition and Behavioral Intention have a positive and significant influence on Use Behavior